Peningkatan Ekonomi Masyarakat Desa Borani Melalui Inovasi Pengolahan Keripik Batang Pisang (BAPIS) - Estherlina Sagajoka; Reyna Virginia Nona; Yuliana Nensi Antonia; Devikarlinda Gobhe (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2021)
Borani Village, Bajawa District, Ngada Regency is a village that has a population of 1,136 people, with the livelihood of most of the people being farmers. Borani village also has a variety of potential natural resources that are quite potential to be developed such as banana plants. Banana plant is a plant from the gardens of the people of Borani Village which is quite potential but until now it has not been developed properly to increase the income of the village community. The people of Borani Village have not made good use of the banana plant because the banana midrib has not been processed into food because it is only used as fodder for livestock. People only know that bananas are used as snacks or sold in logs, and the leaves are used for wrapping containers for making cakes and so on. Based on this situation analysis, the service activities of lecturers and students took the initiative to provide innovative training on the use of Banana Trunks into Banana Trunk Chips (Bapis Chips) so that the utilization of banana stems that had no economic value so far could be increased through innovation in the manufacture and processing of Banana stems into Chips. Bapis as a snack food for children and adults. The innovation of making Bapis chips will provide added value economically for the Borani village community, Bajawa sub-district. The materials and tools used for making bapis chips are easy to obtain and the manufacturing process is very easy and can be done individually or in groups. The training activities for making Bapis Chips went smoothly and there was involvement and activity of the target group during the training activities. This training activity is one of the entrepreneurial activities for the people of Borani Village, Bajawa District,Ngada Regency and is expected to increase the income of the community.